(Self-)Censorship and Nazification: Literary Translation in Occupied Norway (1940-1945) - Solberg, Ida (TTR)

(untitled) (Association canadienne de traductologie, 2021)
This article presents some research on translation during the occupation of Norway by Nazi Germany (1940-1945). It seeks to add new insight to the body of knowledge from recent research that has drawn attention to literary translation during wartime or under military occupation in countries such as Belgium, Germany, and France. Focusing on the regulation of translated literature that was implemented by Nazi authorities during the occupation, the article first describes the process of how this regulation came about and, second, how publishers interacted with Nazi officials in their attempts to navigate the new policy. The main source of data is archival material from the Nazi-installed Ministry of Culture and Popular Enlightenment, notably that of the sub-department for literary affairs, the Literature and Library Office. By investigating this material, the article aims to shed new light both on the particularities of the origin of the censorial system implemented during the occupation of Norway and on its ideological implications, thus adding Norwegian data to previous studies on the politics of translation stemming from Nazi ideology.